The Learning of Toraja Language Variations: The Students' Attitudes, Attendance, Activity Change, and Learning outcomes in Ke'te' Kesu' Toraja Tourism Site Context - Shilfani, Shilfani; Taula'bi', Nilma; Sudarsi, Elim Trika; Girik Allo, Markus Deli; Kristanto, Kristanto (Jurnal Pendidikan Indonesia, 2022)
Language plays an essential role in conveying knowledge and attitudes, including classroom culture. However, local languages ​​are no longer well understood by the younger generation for several reasons, including prestige. This study aims to analyze how changes in students' attitudes, attendance, and activities in learning Toraja language variations in elementary school students and describe student learning outcomes of Toraja language variations in elementary school students. This type of research uses mixed methods. The research design used for qualitative is descriptive qualitative, and quasi-experimental applied quantitatively. The respondents of this study were elementary school students. The research sample selection technique used purposive sampling. Data analysis techniques used are thematic analysis techniques and statistical techniques. The results of this study indicate that, in general, the results achieved by students after the implementation of the Toraja Language Variation Learning learning process for elementary school children at the Ke'te' Kesu' Toraja tourist location can provide an increase both in changes in student attitudes, activeness, attention, and motivation in completing assignments. Student learning outcomes in the variation of Toraja language learning in elementary school students at the Ke'te' Kesu' Toraja tourist location are in a suitable category. In applied linguistics, this research provides new vocabulary related to social context. This study provides local oral literature as an insight for students to expand their knowledge of literary works.